Traditional food plants of the upper Aswa River catchment of northern Uganda—a cultural crossroads - Masters, E.T. (Springer, 2021)
In the parkland agroforestry system of northern Uganda, smallholder farming households rely on a diversity of plant species to fulfil their nutritional requirements, many of which also serve a range of medicinal, cultural, and livelihood functions. The purpose of the study was to assemble an inventory of indigenous plant species used as food in four districts within the Aswa River catchment of northern Uganda, and to document their utilization and management by rural communities. From July 1999 to August 2000, a series of 61 community-based focus group discussions on the utilization of plant biodiversity were conducted in the vernacular language at 34 sites in four districts of northern Uganda, with participation by key informants self-selected on basis of their technical knowledge and personal interest. Of these, 232 respondents subsequently contributed to a collection of herbarium specimens, which were submitted to the Makerere University Herbarium for identification. On receipt of each specimen collected, a structured interview was conducted to document the botanical, ecological, seasonal, and alimentary attributes of each identified taxon, and details of its processing and utilization by the community from which it was obtained. The data analysis was undertaken during 2019 and 2020, including statistical tests to assess the relative importance of the cited taxa using the Relative Importance Index (RI), and to determine the similarity of edible plant use between the four cultures using the Jaccard Index of similarity (JI). Key informant interviews yielded 1347 use reports (URs) for 360 identified specimens of 88 indigenous edible plant species. The data describes patterns of use of indigenous edible plants of four cultures of the Aswa River catchment of northern Uganda. RI scores ranged from 0.93 to 0.11, with fruit trees occupying the top 25 taxa (RI 0.45 and above). Jaccard similarity scores ranged from 25.8% between Lango and Acholi, to 15.8% between Acholi and Ethur, indicating that cultural factors appear to be more significant than shared ancestry as determinants of cultural similarity of plant use. The data constitute an inventory of on-farm plant species, including cultivated, semi-cultivated, and wild plants, integrated into a parkland agroforestry system in which useful trees and other plant species are sustained and managed under cultivation. Agricultural and on-farm plant biodiversity may be seen as a food security resource, and a nutritional buffer against increasing risks and stressors on low-input smallholder agriculture. Further studies should assess the intra-species biodiversity of these resources, with respect to farmer-valued traits and vernacular (folk) classification systems.